A 6th Vital Sign—Potential Use of Nasogastric Tube for Intra-abdominal Pressure Monitoring Method to Detect Feeding Intolerance in Very Low Birth-Weight Preterm Infants (<1500 g). (June 2015) - Carter, Brigit M.; Howard, Christina
Abstract : Background: While various feeding strategies designed to optimize growth have been investigated and used in the clinical setting, the problem of not being able to recognize the warning signs of feeding intolerance early enough to prevent serious gastrointestinal complication commonly associated with very low birth-weight (VLBW) preterm infant remains. Currently, early stages of feeding intolerance are most often identified though nurse assessments. Additional methods to predict feeding intolerance in this population are needed. Currently, intra-abdominal pressure monitoring has been an effective method to predict intolerance to enteral nutrition in the adult and pediatric populations. Purpose: There is supportive evidence for the use of noninvasive methods, such as nasogastric tubes, to effectively monitor IAP. While this may not be the gold standard method of using Foley catheters for measurement, it could provide predictive levels that are indicative of progression toward bowel inflammation. Findings: This review shows the potential for using noninvasive nasogastric tubes for monitoring intra-abdominal pressure and may provide direction for evaluating intra-abdominal pressures in VLBW preterm infants as a reliable method for early identification of feeding intolerance. Implications for Practice: The use of nasogastric tubes to monitor intra-abdominal pressure may provide an effective noninvasive tool to identify VLBW preterm infants progressing toward feeding intolerance and would add to assessment data. Implications for Research: Development and testing of a reliable nasogastric tube monitoring device in the VLBW preterm infant population and identify predictive levels that indicate progression toward feeding intolerance is needed. Once IAP predictive levels are identified, provider interventions could be developed.